ANALYZING INTERNET VOTING SECURITY. - Jefferson, David; Rubin, Aviel D.; Simons, Barbara; Wagner, David (Communications of the ACM, 2004)
This article analyzes the security of Internet voting. The Secure Electronic Registration and Voting Experiment (SERVE) is an Internet-based voting system built by Accenture and its subcontractors for the U.S. Department of Defense Federal Voting Assistance Program (FVAP). The mission of FVAP is to reduce voting barriers for all citizens covered by the Uniformed and Overseas Citizens Absentee Voting Act (UOCAVA), namely U.S. citizens who are members of the military services, their family members, and nonresident U.S. citizens. SERVE is intended to allow UOCAVA voters both to register to vote and to vote via the Internet, from anywhere in the world. To participate, an eligible voter first enrolls in the SERVE program. After enrollment, the voter may register to vote, and then vote in one or two short sessions from any Internet-connected PC. The PC must run a Microsoft Windows operating system and either the Internet Explorer or Netscape Web browser. Because the Internet is independent of national boundaries, an election held over the Internet is vulnerable to attacks from anywhere in the world.